2020
DOI: 10.12659/ajcr.920685
|View full text |Cite
|
Sign up to set email alerts
|

Factor X Deficiency Management for Elective Cesarean Delivery in a Pregnant Patient

Abstract: Rare co-existance of disease or pathology Background:Congenital factor X deficiency is a rare inherited coagulopathy. Pregnancies in women with this disorder are often associated with adverse outcomes, including miscarriage, premature labor, and hemorrhage during pregnancy and in the peripartum period. The literature on this disorder is sparse and shows a limited number of successful pregnancies in women with factor X deficiency. Case Report:In this report, we present the case of a successful pregnancy and ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…FFP (15–25 mL/kg) may be an alternative if PCC is not available. Coagadex® (plasma‐derived FX concentrate) can be used to increase the plasma FX level to 20–50 IU/dL 48 …”
Section: Fx Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…FFP (15–25 mL/kg) may be an alternative if PCC is not available. Coagadex® (plasma‐derived FX concentrate) can be used to increase the plasma FX level to 20–50 IU/dL 48 …”
Section: Fx Deficiencymentioning
confidence: 99%
“…Coagadex ® (plasma-derived FX concentrate) can be used to increase the plasma FX level to 20-50 IU/dL. 48…”
Section: Management Of Pregnancy and Deliverymentioning
confidence: 99%
“…The American Society of Anesthesiologists (ASA) Task Force on perioperative blood Management declares that FFP indicates or improves excessive microvascular bleeding conditions. 12…”
Section: Genetic Polymorphisms In Factor X Deficiencymentioning
confidence: 99%
“…F10, Factor X, is a vitamin K-dependent glycoprotein and also a pivotal coagulation factor in the common coagulation pathway that converts prothrombin to thrombin in the presence of factor Va, calcium, and phospholipid during blood clotting [39]. Factor X deficiency (FXD) is a rare coagulation with manifestation of variable severity and usually increase the risk of bleeding complications [40]. It is reported that heavy menstrual bleeding (HMB), recurrent ovulation bleeding with hemoperitoneum, and bleeding complications in pregnancy are more common in women [41].…”
Section: Screened Hub Nodementioning
confidence: 99%